Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1977
DOI: 10.1007/bf02010618
|View full text |Cite
|
Sign up to set email alerts
|

The combined relationship of temperature and molybdenum concentration to nitrogen fixation byAnabaena cylindrica

Abstract: The joint effects of growth temperature, incubation temperature, and molybdenum concentration on the nitrogen fixation rate ofAnabaena cylindrica were determined using the acetylene-reduction technique. The nitrogen-fixation response to increased molybdenum concentration varied among three growth temperatures (15°, 23°, and 30° C). The pattern of rate change was similar within a growth temperature but increased overall in magnitude with the three incubation temperatures (also 15°, 23°, and 30° C). The maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
2
3
0
Order By: Relevance
“…However, both Chl a concentrations and N 2 -fixation rates required time periods of weeks to decline (Fig. 1), consistent with previous studies (Fay and Vasconcelos 1974;Jacob and Lind 1977). This lag time suggests HC may maintain adaptive strategies, such as stores of cellular Mo, that allow them to survive on low Mo availability for weeks after Mo concentrations are depleted (see below).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, both Chl a concentrations and N 2 -fixation rates required time periods of weeks to decline (Fig. 1), consistent with previous studies (Fay and Vasconcelos 1974;Jacob and Lind 1977). This lag time suggests HC may maintain adaptive strategies, such as stores of cellular Mo, that allow them to survive on low Mo availability for weeks after Mo concentrations are depleted (see below).…”
Section: Discussionsupporting
confidence: 88%
“…This lag time suggests HC may maintain adaptive strategies, such as stores of cellular Mo, that allow them to survive on low Mo availability for weeks after Mo concentrations are depleted (see below). Our data indicate that 10 nmol Mo L 21 is sufficient for maximal N 2 -fixation in the two Nostoc species studied, as previously observed for other HC such as A. cylindrica (Jacob and Lind 1977) and A. variabilis ATCC 29413 (Zerkle et al 2006). The maximal N 2 -fixation rates measured in this study (, 8 nmol C 2 H 4 mg Chl a 21 h 21 ) are comparable to N 2 -fixation rates of A. variabilis ATCC 29413 and A. cylindrica (Attridge and Rowell 1997;Rowell et al 1998).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Culturing experiments with modern strains of diazotrophic (nitrogen-fixing) cyanobacteria generally indicate that rates of nitrogen fixation and overall growth become impacted by Mo availability once concentrations fall to within the ∼1-10-nM range (45)(46)(47)(48)(49). Some strains seem to show resilience to Mo scarcity until concentrations fall below ∼5 nM (48), but in general there seems to be a sharp change in overall growth rates, cell-specific nitrogen fixation rates, and stoichiometric growth status within the 1-10-nM range.…”
Section: Marine Euxinia: Global Effects Of Regional Ocean Chemistrymentioning
confidence: 99%
“…Since Bortels' early studies, Nostoc / Anabaena and Azotobacter strains have been model organisms for the study of Mo requirements for N 2 fixation. Subsequent studies showed that Anabaena had optimal growth at dissolved Mo concentrations in the range of 50–2000 nM (Wolfe, 1954 ; Jacob and Lind, 1977 ; ter Steeg et al, 1986 ; Attridge and Rowell, 1997 ) and that Mo limitation of N 2 fixation occurred at 1–5 nM Mo (Fay and Vasconcelos, 1974 ; Attridge and Rowell, 1997 ; Zerkle et al, 2006 ; Glass et al, 2010 ). The onset of Mo limitation requires several transfers to ensue, likely due to the expression of high-affinity ModABC MoO 2− 4 uptake systems, which are widely distributed in bacteria and archaea (Self et al, 2001 ; Zhang and Gladyshev, 2008 ) and have been characterized in Nostoc/Anabaena (Thiel et al, 2002 ; Zahalak et al, 2004 ).…”
Section: Pure Culture Studiesmentioning
confidence: 99%